Incorporating societal expectations into seismic performance objectives in building codes. Issue 4 (November 2020) - Tanner, Alexa; Chang, Stephanie E; Elwood, Kenneth J
Seismic provisions in building codes arguably constitute the most important and effective means for improving the performance of the built environment during earthquakes. Because they serve as the minimum and mandatory requirements for new construction that accumulates over time, building codes can and have reduced disaster risk in cities around the world; moreover, codes have evolved with improvements in scientific and engineering understanding, technology, and professional standards. Yet many have questioned whether the "life safety" objectives used in codes around the world are adequate or appropriate. In this opinion paper, we argue that seismic code objectives should reflect how society expects the built environment to perform in an earthquake. Social science methods can be employed to overcome the challenges of understanding what standards society holds for seismic performance. This opinion paper suggests four guiding principles on eliciting public perspectives and reviews examples of how elicitation has been applied around the world in the natural hazards field. It concludes with recommendations and further research needs.